Board Diversity And Board Monitoring On Performance Of Malaysian Acquiring Companies: The Interaction Effect Of Board Monitoring Intensity - Osman, Nora (2024)
This thesis is an empirical investigation which is emphasizing on board diversity, board monitoring mechanism and board monitoring intensity (bmi) on performance among acquiring companies in malaysia (m&as). Specifically, this study investigates the association of board diversity and board monitoring toward firm performance. In addition, this study also analyses whether bmi can enhance the relationship between board diversity and firm performance. The findings of this study indicate whether board diversity and board monitoring can increase the performance of acquiring companies in malaysia. Recent research in board structure has focused primarily upon diversification of board of directors in firm performance. A number of studies in developed and emerging countries have carried out to investigate the effect of board diversity on firm performance for public listed and non-listed companies, small and medium enterprises, family companies and financial institutions, but lack of research study on merger and acquisition firms (m&as). This study chooses m&a companies as a sample due to these companies face internal challenges that primarily are related to the management of people. In addition, this study investigates a complementary perspective which is a diversity dimension of company’s directors. Board diversity mechanisms that used in this study are women directors, independent director education, foreign directors and multiple directors, while proxy of board monitoring are independent directors, independent audit committee and the number of board meeting.